Contributions of discourse analysis models to devel-op doctoral and postdoctoral research - Villasmil, Yeriling; Fuenmayor, Gloria (Omnia, 2024)
The knowledge of discourse studies has become a vitally important instrument to develop research in any discipline of knowledge, from this methodology, interdisciplinary or transdisciplinary field, has generated a large amount of research. For this reason, the objective of this study was to analyze the contributions that knowledge of this discipline has had for doctoral and postdoctoral studies and therefore to develop scientific research. The theoretical foundation was based on authors such as: Habermas (1980), Van Dijk (1980, 1999), Franco (2007), Molero and Cabeza (2006), Villasmil and Fuenmayor (2013) Fuenmayor and Villasmil (2015, 2016). The methodology used was of a documentary descriptive nature, since it consisted of describing and comparing three discourse analysis models to highlight their importance in fourth level studies. The results showed that these models or ways of analyzing discourse allow the researcher to develop works whose purpose is to go beyond the meanings present in a text/discourse. It is concluded that every researcher must know the different methodologies of discourse analysis